Eksplorasi Sinergi Pendekatan Fitoremediasi dan Ameliorasi dalam Rehabilitasi Tanah pada Lahan Pascatambang - Melati Ambarita, Debora Dellaocto; Nurrulhusna, Nabila; Azizah, Azizah (Soilrens, 2025)
Soil degradation due to mining activities has led to a significant decline in environmental quality, with the mining sector contributing to deforestation of 29,635 hectares and critical land in Indonesiareaching 12.7 million hectares. Additionally, heavy metal contamination has caused a 75% decreasein soil fertility, posing a threat to ecosystem health and human well-being. This study aims to explorethe effects of phytoremediation and amelioration on the rehabilitation of post-mining soils to enhancesoil health. The article employs a systematic literature review approach using PRISMA guidelines andbibliometric use VOSviewer 1.6.19 version analysis through Scopus search engine. A systematic reviewwas conducted on studies published between 2016 and 2026, and out of 1,942 identified articles, 15were deemed eligible for inclusion. The findings indicate that the synergy between phytoremediationand amelioration has significant potential in the recovery of post-mining soils contaminated withheavy metals. Phytoremediation plants such as Rumex nepalensis, which can accumulate heavy metalsup to 100%, have proven to be effective in reducing soil contamination. Moreover, ameliorants suchas biochar and compost can reduce the bioavailability of heavy metals by up to 75%, while improvingsoil quality by enhancing soil structure, raising pH, and supporting plant growth. The combination ofthese approaches creates more favorable conditions for plant growth, thereby accelerating therehabilitation of soils and ecosystem recovery. The appropriate selection of plant species andameliorants can significantly improve the efficiency and sustainability of post-mining soil restoration,offering a long-term solution to environmental degradation caused by mining activities.